Pulmonary vasculature development in congenital diaphragmatic hernia: a novel automated quantitative imaging analysis - Aydin, Emrah; Durmus, Furkan; Torlak, Nilhan; Oria, Marc; Bayazit, Nilguen Guler; Isik, Esin Oztuerk; Aslanyurek, Birol; Peiro, Jose L. (SPRINGER, 2024)
PurposeImpaired fetal lung vasculature determines the degree of pulmonary hypertension in the congenital diaphragmatic hernia (CDH). This study aims to demonstrate the morphometric measurements that differ in pulmonary vessels of fetuses with CDH.MethodsNitrofen-induced CDH Sprague-Dawley rat fetuses were scanned with microcomputed tomography. The analysis of the pulmonary vascular tree was performed with artificial intelligence.ResultsThe number of segments in CDH was significantly lower than that in the control group on the left (U = 2.5, p = 0.004) and right (U = 0, p = 0.001) sides for order 1(O1), whereas there was a significant difference only on the right side for O2 and O3. The pooled element numbers in the control group obeyed Horton's law (R2 = 0.996 left and R2 = 0.811 right lungs), while the CDH group broke it. Connectivity matrices showed that the average number of elements of O1 springing from elements of O1 on the left side and the number of elements of O1 springing from elements of O3 on the right side were significantly lower in CDH samples.ConclusionAccording to these findings, CDH not only reduced the amount of small order elements, but also destroyed the fractal structure of the pulmonary arterial trees.
Keywords: Lung vasculature; Microcomputed tomography; Lung development; Fetal pulmonary circulation; Vessel morphology; SKELETAL-MUSCLE; MICRO-CT; LUNG; MORPHOMETRY; MICROVASCULATURE; NETWORK; STANDARDS; PRESSURE; SYSTEM; MODEL; Pediatrics; Surgery